Black Lesbian Spirituality: Hearing Our Stories - Elana C. Betts (Adult Education Research Conference, 2012)
This paper examines the intersection of race, gender, sexual orientation and spirituality, specifically Black lesbian spirituality. One of the difficulties in citing current research is the dearth of published research on the spirituality of women of color, who identify a sexual minority. There have been many studies and books written about spirituality, culture, gender and sexuality, however the study of Black lesbian spiritual identity remains largely untouched. The purpose of this study is to explore how spiritual development and the expression of spirituality is connected to the African American lesbian culture through narrative inquiry meets autoethnography. The findings indicate that Black lesbian spiritual development is largely inspired by the influence of spiritual facilitators and spiritual constrictors that create a fluid balance, defined as spiritual wholeness.